Textile Patterns and Their Epistemological Functions - Kraft, Kerstin

In situ Synchrotron SAXS/XRD Study on the Formation of Ordered Mesoscopic Hybrid Materials with Crystal-Like Walls - Morell, Jürgen; Teixeira, Cilaine V.; Cornelius, Maximilian; Rebbin, Vivian; Tiemann, Michael; Amenitsch, Heinz; Fröba, Michael; Lindén, Mika (Chemistry of Materials)
In situ Synchrotron SAXS/XRD Study on the Formation of Ordered Mesoscopic Hybrid Materials with Crystal-Like Walls...

Ätztechnik - Hilleringmann, Ulrich (Silizium-Halbleitertechnologie)
In der Halbleitertechnologie werden die Materialien Siliziumdioxid, Siliziumnitrid, Polysilizium, Silizium, Aluminium sowie Wolfram und Titan mit ihren jeweiligen Metallsiliziden geätzt. Die Ätztechnik dient dabei zum ganzflächigen Abtragen eines Materials oder zum Übertragen der Struktur des lithografisch erzeugten Lackmusters in die darunter liegende Schicht. Für diese Aufgabe bieten sich einerseits nasschemische Ätzlösungen an, zum anderen eignen sich speziell entwickelte Trockenätzverfahren zur geforderten präzisen Strukturübertragung vom Lack in das Material.

Imprint structured organic thin film transistors as driving circuit in single-use sensor applications - Hilleringmann, Ulrich; Pannemann, C. (Fifth International Symposium on Instrumentation and Control Technology)

Piezoresistive pressure sensors in CVD diamond for high-temperature applications - Otterbach, Ralf; Hilleringmann, Ulrich (Fifth International Symposium on Instrumentation and Control Technology)

Nonlinear optical properties of semiconductor quantum wells inside microcavities - Meier, Torsten; Sieh, C.; Koch, S.W.; Lee, Y.-S; Norris, T.B.; Jahnke, F.; Khitrova, G.; Gibbs , H.M. (Optical Microcavities)
Experimental results on the nonlinear optical properties of semiconductors are compared with microscopic calculations which include Coulomb many-body correlations at different levels. One aim of this chapter is to show that microscopic theories, which have been developed for bare semiconductor heterostructures, are also able to describe semiconductor microcavities very well. Therefore, there is no need to phenomenologically introduce polariton-polariton interactions and parametric scattering of cavity polaritons to describe microcavity experiments, but instead a fully microscopic theory based on a Fermionic electron-hole Hamiltonian can be used. The treatment of many-body correlations using the second-order Born approximation and the dynamics-controlled truncation scheme are introduced and analyzed for bare heterostructures. These approaches are able to successfully explain a number of important experimental results which originate from the dynamics of many-body correlations. Then measurements of the nonlinear optical properties of a quantum-well microcavity are described. In these experiments the spectrally- and temporally-resolved nonlinear optical response is studied in detail using a pump-probe geometry. In particular, the polarization and intensity dependencies of the spectral probe reflection changes and their temporal evolution are analyzed. The prominent features of these experiments are well accounted for by the microscopic many-body theory.

Gerd Nuschmann / Manfred L. Pirner: Werbung, Religion, Bildung. Kulturhermeneutische, theologische, medienpädagogische und religionspädagogische Perspektiven (Beiträge zur Medienpädagogik 8), Frankfurt/M. 2003 - Schroeter-Wittke, Harald (Zeitschrift für Pädagogik und Theologie)

18. Sonntag nach Trinitatis. Eph 5,8b-14: Brüchige Orientierungen - Schroeter-Wittke, Harald (Zeitschrift für Gottesdienst und Predigt)

9. Sonntag nach Trinitatis. Phil 3,7-11(12-14): Vergessen - Schroeter-Wittke, Harald (Zeitschrift für Gottesdienst und Predigt)

Vom Verschwinden eines Ortes als Utopie - Schroeter-Wittke, Harald (Zeitschrift für Gottesdienst und Predigt)